2021
DOI: 10.1093/ageing/afab205
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications and their effect on falls during hospital admission

Abstract: Objective to investigate the effect of potentially inappropriate medications (PIMs) on inpatient falls and to identify whether PIMs as defined by STOPPFall or the designated section K for falls of STOPP v2 have a stronger association with inpatient falls when compared to the general tool STOPP v2. Methods a retrospective observational matching study using an electronic health records dataset of patients (≥70 years) admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…The Beers Criteria, STOPP/START, NORGEP, and PRISCUS are representative guidelines ( Rognstad et al, 2009 ; Holt et al, 2010 ; O’Mahony et al, 2015 ; By the American Geriatrics Society Beers Criteria Update Expert, 2019 ). The use of PIMs in older adults is associated with ADRs, falls and fractures, hospitalizations, and increased healthcare costs ( Hyttinen et al, 2016 ; Damoiseaux-Volman et al, 2021 ; Yadesa et al, 2021 ). Thus, medication management to evaluate and prevent PIM use in older adults is important.…”
Section: Introductionmentioning
confidence: 99%
“…The Beers Criteria, STOPP/START, NORGEP, and PRISCUS are representative guidelines ( Rognstad et al, 2009 ; Holt et al, 2010 ; O’Mahony et al, 2015 ; By the American Geriatrics Society Beers Criteria Update Expert, 2019 ). The use of PIMs in older adults is associated with ADRs, falls and fractures, hospitalizations, and increased healthcare costs ( Hyttinen et al, 2016 ; Damoiseaux-Volman et al, 2021 ; Yadesa et al, 2021 ). Thus, medication management to evaluate and prevent PIM use in older adults is important.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, our findings are not consistent with studies conducted in European countries who reported a lower prevalence of PIM using BC. 16,[34][35][36] One study conducted in Ireland examined the association between the detected PIM and ADEs in patients aged ≥65 years in hospitals. 16 That study revealed the prevalence of PIM prescriptions to be 28.8% by applying BC.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the PPV, we would rather suggest to explore strategies for excluding drugs with a relatively low risk on the clinical event. A recent observational study compared the association of potentially inappropriate medication on inpatient falls listed in the explicit screening tools STOPP v2, STOPP v2 section K, and STOPPFall [ 26 28 ] Although all screening tools were independently associated with falls, the strongest effect was identified for STOPP section K [ 28 ]. This is plausible because STOPP section K is the most restrictive tool, including only four drug classes with highest risk of falls (i.e.…”
Section: Discussionmentioning
confidence: 99%